Pertautan Agama Dan Budaya Dalam Keislaman Komunitas Piti Jepara - Nur Kholis (Sabda: Jurnal Kajian Kebudayaan, 2019)
This study aims to identify variants of Islamic religiosity in Chinese Muslim life as reflected in the organization of the Indonesian Chinese Islamic Association (Persatuan Islam Tionghoa Indonesia/PITI). This organization has distinctive features about how dialogue between Islam, Chinese ethnicity, implementation of Indonesian Islamic law legislation, and Javanese culture occured. This study uses a symbolic-interpretative anthropology approach. The conclusion of this study includes as the following (1) the organizational system of PITI in Jepara district is driven by indigenous Muslims who are active as administrators of the Nahdlatul Ulama in Jepara district and only two people of Chinese descents are administrators, while others are members; on the other hand, the involvement of "influential people" in the political world in Jepara also supports its existence. As for the organization funding is obtained and managed independently in the management level in Jepara; (2) Islamic characteristics of the PITI Muslim community in Jepara regency include muallaf status, feeling of being a minority but having sufficient economic, secular-materialist tendencies, prominent Chinese culture, and still strong pressure from family circles for Islam; and (3) the dimensions of Chinese socio-culture and the lives of indigenous people are more visible in socio-cultural life than the influence of religious norms.